Effect of osteoporosis on periodontal therapy among post‐menopausal women. (16th March 2012) - Gomes‐Filho, Isaac S.; Oliveira, Tiago J. S.; Passos, Johelle S.; Cerqueira, Eneida de M. M.; da Cruz, Simone S.; Barreto, Maurício L.; Coelho, Julita M. F.; Trindade, Soraya C.; Santos, Carlos A. S. T.; Sarmento, Viviane A.
Abstract : Objective: This intervention study aimed to investigate the effect of osteoporosis on periodontal condition among 48 post‐menopausal women undergoing periodontal therapy. Material and methods: The experimental group, which underwent non‐surgical periodontal therapy, was composed of 16 women with periodontitis to be treated, and the control group was formed by 32 women without periodontitis. Oral condition was assessed on three occasions: at the start of the treatment (first examination), 1 month (first re‐examination) and 4 months after the end of the therapy (second re‐examination). In the second re‐examination, recurrence of periodontal disease was evaluated by comparing the clinical measurements obtained pre‐ and post‐treatment. The diagnosis of osteoporosis was made by investigating densitometry reports obtained previously. Descriptive analysis, analysis of variance and the Bonferroni post hoc test were applied to the data gathered, with statistical significance level of 5%. Results: The frequency of periodontitis was 50% in the treated group and 25% in the group without periodontitis. In both groups, this recurrence was greater in subjects with osteoporosis (37.5 and 18.75%, respectively) than in the individuals without osteoporosis (12.5 and 6.25%, respectively). Conclusions: The preliminary results indicate that osteoporosis possibly has an influence on periodontal condition among individuals undergoing non‐surgical periodontal treatment.